An automatic detection method for 40-Hz auditory steady state response and its application in prognosis of comatose patients. Issue 3 (March 2020) - Chen, Tingting; Lu, Shiqi; Qian, Ping; Chen, Guolin; Hu, Nan
Highlights: Four 40-Hz auditory steady-state response (ASSR) stimulation paradigms were employed. A 40-Hz ASSR detection algorithm was proposed to achieve automatic detection. Combining the 40-Hz ASSR paradigms gave a more precise coma outcome prediction. Abstract: Objective: We proposed a 40-Hz auditory steady-state response (ASSR) automatic detection method, and studied the prognosis of comatose patients by combining the 40-Hz ASSR detection results of multiple paradigms of auditory stimulation. Methods: The 40-Hz ASSR elicitation experiments were carried out on 32 comatose patients, with the detection results used as prognosis predictors. To achieve automatic detection, the detection was modeled as a binary hypothesis test for a sinusoidal waveform with unknown amplitude and phase, based on the generalized likelihood ratio test (GLRT). The patients were followed up for 6 months, and each patient's outcome was classified as either favorable outcome (severe disability, moderate disability or good recovery) or unfavorable outcome (vegetative state/unresponsive wakefulness syndrome or death) according to the Glasgow outcome scale (GOS). The performance of the prognosis predictors was assessed using the area under the receiver operating characteristic curve (AUC-ROC). Results: The largest AUC in univariate analysis involving a single stimulation paradigm was 0.849, while the AUC obtained by combining multiple predictors was increased to 0.966. Conclusions: For comatose patients, the absence of 40-Hz ASSR in multiple stimulation paradigms may indicate an unfavorable prognosis. Furthermore, the combination of multiple auditory stimulation paradigms may increase the outcome prediction accuracy. Significance: The combination of multi-paradigm 40-Hz ASSR automatic detection results may provide a feasible automatic outcome prediction method for comatose patients.